Palpable lesions as a diagnostic tool in patients with thoracic pathology. Issue 1 (16th June 2011) - Yener, Nese Arzu; Midi, Ahmet; Cubuk, Rahmi; Orki, Alpay; Onar, Cagatay; Ersev, Ayse; Arman, Bulent
Abstract Palpable lesion(s) noticed in a patient with thoracic disease may be a useful diagnostic tool and it often gives a clue for further management. In this study, we searched the diagnostic value of palpable lesions in patients with thoracic pathology suspected clinically and/or radiologically. We prospectively examined the correlations of clinical/radiologic and pathologic findings of 72 palpable lesions from 68 patients who presented with suspect for a thoracic disease from two tertiary medical centers. Thirty‐two lesions (44.4%) were diagnosed as malignant either by fine‐needle aspiration (FNA) only or FNA with confirmatory biopsy. The most common malignancy was non‐small‐cell carcinoma (10) followed by adenocarcinoma (6), and small‐cell carcinoma (5). The most common localization of the palpable lesions was cervical region (20.8%) followed by left supraclavicular (13.8%) and anterior chest wall (13.8%). FNA was effective in obtaining an accurate diagnosis in 66.6% of the patients. Tissue confirmation of FNA was performed in 54 patients. The sensitivity, specificity, negative predictive value, and positive predictive value of FNA in distinguishing a malignant lesion from a benign disease for these palpable lesions were 75, 97, 96, and 80, respectively. One false negativity and one false positivity were also found. Abnormal radiologic features were not correlated with having a malignant palpable lesion. Evaluation of the palpable lesions by FNA and tissue biopsy together is effective for initial triage of the patients with suspect for a thoracic pathology. FNA alone is a convenient and easy method for this purpose especially when the material is immediately assessed for specimen adequacy. Diagn. Cytopathol. 2013. © 2011 Wiley Periodicals, Inc.